Elevated serum Cripto‐1 and VEGF levels in patients with non‐small cell lung cancer. Issue 8 (3rd May 2022) - Xu, Chunhua; Zou, Jue; Li, Li; Yuan, Qi; Wang, Wei
Abstract: Cripto‐1 (CR‐1) facilitates vascular endothelial growth factor (VEGF) expression, and these markers are associated with various tumor cell proliferation, angiogenesis, and metastasis. The main aim of our study was to investigate the clinical value of CR‐1 and VEGF for non‐small cell lung cancer (NSCLC) patients. Serum samples were collected from 312 patients with NSCLC and 120 healthy controls. The levels of CR‐1 and VEGF were measured by enzyme‐linked immunosorbent assay (ELISA). The serum levels of CR‐1 and VEGF in NSCLC patients were significantly higher than those of healthy controls ( p  < 0.05). Elevated CR‐1 levels were associated with progression of NSCLC stage and higher CR‐1 was detected more in patients with distant metastasis ( p  < 0.05). Patients exhibiting low levels of serum CR‐1 had better overall survival than those with high levels ( p  < 0.05). The CR‐1 levels of NSCLC patients with postoperative recurrent were higher than those of nonrecurrent NSCLC patients. Our study suggests that serum CR‐1 and VEGF are useful biomarker for NSCLC patients.